Towards carbon neutrality in construction projects based on life cycle assessment - Nguyen Van Son; Pham Ngoc Thinh; Le Trung Phong; Bui Le Khanh (Tạp chí Khoa học và Công nghệ)
The construction industry is among the largest global consumers of natural resources and contributors to greenhouse gas emissions. This paper aims to evaluate current environmental standards and propose a new framework for reducing greenhouse gas emissions, targeting carbon neutrality in construction projects. The study employs the Life Cycle Assessment (LCA) methodology to assess the environmental impacts of civil buildings throughout their lifecycle, including material production, construction, operation, and disposal. Data were obtained from the IMPRO-Building project, which analyzed 72 building samples across three distinct climate zones in Europe. The findings indicate that high-rise buildings demonstrate greater energy efficiency compared to single-storey and multi-storey structures. Furthermore, climatic conditions significantly influence energy consumption, with cold climates exhibiting higher energy demands. The study recommends adopting LCA-based standards to mitigate environmental impacts, thereby promoting the sustainable development of the construction industry.